2014
DOI: 10.1007/8904_2014_360
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Profiles of Children with Glutaric Aciduria Type I Diagnosed by Newborn Screening: A Follow-Up Case Series

Abstract: Glutaric aciduria type I (GA-I) is an inherited metabolic disorder that may lead to severe motor disorder and cognitive impairment. GA-I is now included in the newborn screening programme in many countries as early detection allows for prompt treatment and effectively reduces the risk of poor developmental outcome. Information regarding the long-term neurodevelopmental outcome of children with GA-I treated early is sparse.We recruited children with a confirmed diagnosis of GA-I diagnosed via newborn screening,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…SRT (slower in dystonic patients) and VWM (similar results in patients and controls) are on the extremes of the speed vs. cognitive demand dimension of our tests and the pattern of our results, speed being affected in dystonic patients, and VWM performance being normal in dystonic as well as asymptomatic patients, supports the hypothesis that intellect might be preserved in GA-I [ 32 ], and neurological disease manifestation may be limited to dystonic movement disorder or subtle neurological abnormalities. In line with our findings Brown et al [ 33 ] recently showed that IQ scores and executive functioning were normal in six GA-I patients diagnosed by newborn screening. Our concept of working memory does not include the cognitive manipulation of the stored stimulus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…SRT (slower in dystonic patients) and VWM (similar results in patients and controls) are on the extremes of the speed vs. cognitive demand dimension of our tests and the pattern of our results, speed being affected in dystonic patients, and VWM performance being normal in dystonic as well as asymptomatic patients, supports the hypothesis that intellect might be preserved in GA-I [ 32 ], and neurological disease manifestation may be limited to dystonic movement disorder or subtle neurological abnormalities. In line with our findings Brown et al [ 33 ] recently showed that IQ scores and executive functioning were normal in six GA-I patients diagnosed by newborn screening. Our concept of working memory does not include the cognitive manipulation of the stored stimulus.…”
Section: Discussionsupporting
confidence: 93%
“…The general assumption is that intellect is spared in GA-I [ 32 ]. In fact, normal cognitive function was reported, however, studies had only small sample sizes and no control group [ 33 ]. However, decreased IQ or more subtle cognitive deficits were also reported for a few children with GA-I [ 34 , 35 ] and cognitive decline was found in late-onset GA-I patients [ 26 ], The few studies on cognitive function in GA-I only focussed on IQ but not on development of cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of striatal injury is most pronounced up to age 6 years when dietary controls are most strict; thereafter, there is more scope for some relaxation in some cases 33 . Adherence to these guidelines is associated with improved neurological outcome 5,36 . The neurological sequelae are managed with baclofen or diazepam for movement and tone disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was observed that early neuropsychological and speech assessments and therefore speech therapy improved speech in GA1 patients. 11 These show that in addition to dietary management and medical therapy initiated in GA1 patients, appropriate therapies can make the outcome of patients more favourable.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was suggested that patients with neuropsychological and speech assessments be done early on so that early and appropriate intervention may be done. 11 In addition to carnitine supplementation, anti-dystonia drugs and AEDs had been used in GA1 patients. Of our 7 patients, only patient 5 was prescribed with baclofen, which is one of the most widely used drug for dystonic movements in GA1.…”
Section: Discussionmentioning
confidence: 99%